On the taxonomy of Afrotropical Coleophoridae (IV). New or little known species from South Africa (Lepidoptera, Coleophoridae) - Baldizzone, Giorgio; van Der Wolf, Hugo W. (Zootaxa, 2020)
The paper deals with ten species of Afrotropical Coleophoridae from South Africa and Swaziland. For one previously described species, Coleophora halmodes Meyrick, 1911 a lectotype is designated and the genitalia are illustrated for the first time. Nine new species of Coleophora Hübner, 1822 are described: C. stenoptera, sp. nov., C. swaziella, sp. nov., C. armata, sp. nov., C. suavis, sp. nov., C. venusta, sp. nov., C. hirtella, sp. nov., C. deinosella, sp. nov., C. intorta, sp. nov., C. leptella, sp. nov.